Pengaruh Pertumbuhan Ekonomi, Investasi Dan Upah Minimum Terhadap Tingkat Pengangguran Di Provinsi Maluku Utara - Yetty Yetty; Resmiyati Ansar (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
The study analyses the determinants of unemployment in North Maluku". The study using such variables as unemployment, economic growth, investment, and local minimum wage. The data analyzed quantitatively by conducting the statistical method of multiple linear regression. The results show that the economic growth and the minimum wages have a significant effect, otherwise the investment has not significant effect on an unemployment in North Maluku Province. This is caused by the high dependence of North Maluku on supplies from outside the province that led to net imports between regions, and it then induce a negative share for the economic structure of North Maluku.